Perceptions of pregnancy, labour, and post-partum difficulties related with the adoption of focused antenatal care services among women of reproductive age in Sirisia Sub-County, Bungoma County, Kenya - Makunja, Tobias; Kariuki, John; Ndwiga, Taratisio (International Journal Of Community Medicine And Public Health, 2024)
Background: Focused antenatal care (FANC) adoption is significantly influenced by women's perceptions of pregnancy, labour, and post-partum difficulties. Cultural beliefs, personal experiences, and social norms shape these perceptions, affecting whether women seek FANC services. Fear of medical procedures and privacy concerns also deter FANC adoption. These perceptions contribute to FANC underutilization, potentially compromising maternal and neonatal health outcomes. Methods: Analytical cross-sectional study design was used and 323 participants in the selected wards in Sirisia subcounty, Bungoma County, Kenya. Data was collected using interviewer administered structured questionnaire, and focus group discussion. Quantitative data analysis was conducted using statistical package for the social sciences (SPSS) version 29.0 and involved univariate and bivariate analysis. Bivariate analysis was done through logistic regression was used to test the significance of the association between the dependent and independent variables (p<0.05). Qualitative data was analyzed by thematic content analysis. Results: More than half 183 (56.7%) had initial prenatal care attendance between 4-6 months and 17 (5.3%) between 7-9 months. Further, 202 (62.5%) had four or more ANC visits with 5 (1.5%) and 85 (26.3%) had one and three visits respectively. Significant relationships were found between FANC uptake and positive perceptions of well-being (OR=5.810), worry alleviation (OR=2.425), complication reduction (OR=5.011), birth preparedness (OR=4.551), service access (OR=3.005), and risk detection (OR=5.847). Barriers included fatigue (66%), permission requirements (67%), and transportation issues (65%). Factors like clinic distance, terrain, waiting times, and staffing shortages significantly influenced FANC uptake (p=0.0001). Conclusions: FANC uptake influenced by perceived benefits and demographics. Logistical challenges remain. Recommendations include mobile clinics and community health worker education to improve access and awareness.